Single-Nucleotide Polymorphisms in LEP and LEPR Associated With Breast Cancer Risk: Results From a Multicenter Case–Control Study in Chinese Females - Li, Liang; Meng, Xingchen; Liu, Liyuan; Xiang, Yujuan; Wang, Fei; Yu, Lixiang; Zhou, Fei; Zheng, Chao; Zhou, Wenzhong; Cui, Shude; Tian, Fuguo; Fan, Zhimin; et al. (Frontiers in Oncology, 2022)
Background Leptin (LEP) plays a physiological role through its specific receptor (LEPR) and is involved in the occurrence and development of breast cancer. Our current study aimed at determining the influence of single-nucleotide polymorphisms (SNPs) in the genes coding for LEP and LEPR on breast cancer risk. Methods In the present study, 963 breast cancer cases and 953 controls were enrolled. Five SNPs of LEP and two of LEPR were chosen to evaluate the correlation of selected SNPs with breast cancer susceptibility among women in northern and eastern China. Analyses were further stratified by body mass index (BMI), waist–hip rate (WHR), estrogen receptor, and progesterone receptor status. The expression patterns of risk variant-associated genes were detected by expression quantitative trait locus (eQTL) analysis with eQTLGen and The Cancer Genome Atlas database. Results There were significant differences between breast cancer cases and control groups in the menopausal status and family history of breast cancer. Two SNPs (rs1137101 and rs4655555) of the LEPR gene decreased overall breast cancer risk, and other five SNPs showed no significant association with breast cancer risk. rs1137101 (GA vs. GG; adjusted OR = 0.719, 95% CI = 0.578–0.894, p = 0.003) and rs4655555 (TT vs. AA; adjusted OR = 0.574, 95% CI = 0.377–0.873, p = 0.009) significantly decreased breast cancer risk after Bonferroni correction for multiple testing. In subgroup analyses, the GA and GA + AA genotypes of LEPR rs1137101 associated with decreased breast cancer risk in the subgroup of BMI ≤ 24 kg/m2 or WHR ≥ 0.85 after Bonferroni correction. Furthermore, we found that the expressions of rs4655555-associated gene LEPR and leptin receptor overlapping transcript (LEPROT) were upregulated in breast cancer tumor tissues compared with adjacent normal tissues, and a higher expression of LEPR in tumor tissues was correlated with poor prognosis of breast cancer patients using The Cancer Genome Atlas Breast Invasive Carcinoma (TCGA-BRCA) data. Conclusion Our study demonstrated that the polymorphisms rs1137101 and rs4655555 located in the LEPR gene decreased breast cancer risk in Chinese females, which might be a research-worthy bio-diagnostic marker and applied for early prediction and risk assessment of breast cancer.